Enhancing Language Skills and Fostering Perspective Transformation in Adult ESL Education: A Transformative Learning Approach - Bruce Manson; Eric Poitras; Yuan-Jin Hong (Adult Education Research Conference, 2010)
The objectives of this action research are to examine how a transformative learning approach in a university-level ESL setting improved the English language skills of two classes of 32 learners, and how this approach influenced their perspectives on a number of issues. Findings indicate that many learners experience significant gains in their English language abilities, increased self-confidence in English, and perspective shifts regarding the language learning process, other cultures, and a number of social issues.